Penerapan Teknologi Stack MERN pada Aplikasi Service Manajemen Bengkel Berbasis Web - Moch. Akbar Maulana; Haryoko Haryoko; Banu Santoso; Lukman Lukman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Xyz Motor is a repair shop engaged in the automotive motorcycle sector by providing services in the form of motorcycle service and spare parts sales. All business processes such as recording of spare parts, sales and purchase transactions of spare parts, as well as television/monthly recapitulation are carried out manually so that business processes take a long time and are inefficient. To overcome the problems experienced by the Xyz Motor workshop, the researchers created a web-based management service application to manage all processes that occur so that it is easier for the workshop to see the entire business process and the owner can improve performance and productivity in recapitulation.The Management Service application was developed using the MERN Stack technology, namely MongoDB for the database, React Js for the frontend library and Node Js with the Express Js library to create the backend API. The application developed includes features for making spare parts, recording daily and monthly reports and creating customer invoices. This Management Service Application Development has succeeded in supporting responsive web design so that workshop owners can access the web from a laptop or smartphone